Myeloid hypoxia-inducible factor HIF1A provides cardio-protection during ischemia and reperfusion via induction of netrin-1 - Heck-Swain, Ka Lin; Li, Jiwen; Ruan, Wei; Yuan, Xiaoyi; Wang, Yanyu; Koeppen, Michael; Eltzschig, Holger K. (Frontiers in Cardiovascular Medicine, 2022)
The transcription factor hypoxia-inducible factor HIF1A induces cardioprotection from ischemia and reperfusion injury. Here, we investigate tissue-specific pathways that are critical for HIF1A-elicited tissue protection. Initial studies showed that mice with induced global Hif1a deletion (Hif1aloxP/loxP UbiquitinCre+) have exaggerated myocardial injury during in situ ischemia and reperfusion. Surprisingly, this phenotype was mirrored only in mice with myeloid-specific Hif1a deletion (Hif1aloxP/loxP LysM Cre+). In contrast, mice with myocardial specific (Hif1aloxP/loxP Myosin Cre+), or vascular Hif1a deletion (Hif1aloxP/loxP VEcadherin Cre+) experienced similar levels of injury as controls. Subsequent studies using adoptive transfer of Hif1a-deficient polymorphonuclear neutrophils (PMNs) prior to myocardial injury demonstrated increased reperfusion injury. On the contrary, the adoptive transfer of PMNs treated ex vivo with the hypoxia inducible factor (HIF) stabilizer dimethyloxalylglycine (DMOG) was associated with attenuated myocardial injury. Furthermore, DMOG-mediated cardioprotection was abolished in Hif1aloxP/loxP LysM Cre+ mice, but not in Hif2aloxP/loxP LysM Cre+ mice. Finally, studies of PMN-dependent HIF1A target genes implicated the neuronal guidance molecule netrin-1 in mediating the cardioprotective effects of myeloid HIF1A. Taken together, the present studies identified a functional role for myeloid-expressed HIF1A in providing cardioprotection during ischemia and reperfusion injury, which is mediated, at least in part, by the induction of the netrin-1 neuronal guidance molecule in neutrophils.